NCAA Drug Testing Policies and Penalties - Kelly P. Elliott; Timothy B. Kellison; Beth A. Cianfrone (University of Kansas Libraries, 2018)
Under National Collegiate Athletic Association (NCAA) rules, all Division I and II student-athletes are subject to year-round drug testing. In addition to these NCAA-mandated tests, the NCAA encourages each member school to establish its own drug testing policy. Drug testing has been studied frequently, often from the legal, athlete motivation, or economic perspectives. Yet, on the collegiate level, it is unclear the extent to which drug testing policies vary across institutions and divisions. Therefore, the purpose of this study was to compare the drug testing policies of high- and low-performing athletic programs to determine whether student-athletes competing on successful teams in revenue-generating sports are held to different standards than those participating on less successful athletic teams. Drug testing policies were collected from "high-performing" Division I and II athletic programs (i.e., those ranked in the top 25 in football, men's basketball, or women's basketball between 2012-2017); these policies were compared with those of "low-performing" athletic programs (i.e., those ranked in the bottom 50 of the Directors' Cup between 2012-2017). The results indicate several contrasts between high- and low-performing athletic departments in how they penalize athletes for positive drug penalties, particularly at the Division I level.